Journal of Prisoners on Prisons, V34, #1 (Journal of Prisoners on Prisons, 2025)
VOLUME 34, Number 1 (2025) is a special issue of the Journal of Prisoners on Prisons on “Emotions and the Affective Politics of Incarceration” edited by Jennifer M. Kilty (University of Ottawa), Rachel Fayter (Carleton University) and Justin Piché (University of Ottawa). In addition to articles on the emotions, affect and imprisonment, this edition of the journal includes a call for contributions for the 50th edition of Prisoners’ Justice Day, book reviews, and artwork by Steel Door Studios (https://steeldoorstudios.com).